Comparative study between Johnson’s formula and Dare’s formula of fetal weight estimation at term - C., Anitha; Kanagal, Deepa V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Prediction of fetal weight is one of the methods towards effective management of pregnancy and delivery. To assess and compare the accuracy of clinical and sonographic fetal weight estimation in predicting birth weight at term pregnancy, patients who were in latent or in active phase of labour. In the present study, an effort is made to compare two different clinical methods and USG and relate to the actual weight of the baby at birth. Methods: It is a prospective observational study of one hundred pregnant women satisfying the criteria, consenting for the study was recruited. Both USG and clinical methods will be done and compared with estimated the fetal weight. Weight of the baby at birth will be measured. Results: All the three methods had significant relationship with the baby weight. Percentage error was least with USG and the standard deviation of error was lower with Dare’s formula. The standard deviation was minimal for Dare`s formula EFW followed closely by USG. Conclusions: It can be concluded that Dare’s formula of clinical methods can be a potential option to be promoted in predicting the fetal weight in the absence of USG facilities. Training in this method is very important and can be an integral part in managing pregnancy during delivery in primary care setting.